Penguatan kelembagaan desa adat di Kampung Lubuk Jering Kecamatan Sungai Mandau Kabupaten Siak - Abdul Sadad; Dadang Mashur; Tito Handoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This service aims to provide institutional strengthening of traditional villages in the administration, development and service to the community in Lubuk Jering Village, Sungai Mandau District. The problem that occurs is due to increasingly complex systems of life in the midst of indigenous village communities as a result of the influence of urbanization from other regions. Traditional villages in Siak Regency are one form of traditional government system in Indonesia that has undergone many changes. The change concerns various aspects of social life that touch the values, norms, attitudes and patterns of behavior of the people. The method used is the extension method. The implementation of community service in the context of strengthening customary institutions in Lubuk Jering Village, Mandau District can be concluded to have successfully provided counseling. This success was demonstrated, among others, by the compatibility of the material with the needs of village government officials and the community in an effort to strengthen Then there was a positive response (70%) of participants based on the questionnaire distributed, which was indicated by the questions and responses given during the service. Most of the participants understood the importance of strengthening adat institutions in Kampung Lubuk Jering, Sungai Mandau District, Siak Regency.